A Review of Enteric Methane Emission Measurement Techniques in Ruminants - Yiguang Zhao; Xuemei Nan; Liang Yang; Shanshan Zheng; Linshu Jiang; Benhai Xiong (Animals, 2020)
To identify relationships between animal, dietary and management factors and the resulting methane (CH4) emissions, and to identify potential mitigation strategies for CH4 production, it is vital to develop reliable and accurate CH4 measurement techniques. This review outlines various methods for measuring enteric CH4 emissions from ruminants such as respiration chambers (RC), sulphur hexafluoride (SF6) tracer, GreenFeed, sniffer method, ventilated hood, facemask, laser CH4 detector and portable accumulation chamber. The advantages and disadvantages of these techniques are discussed. In general, RC, SF6 and ventilated hood are capable of 24 h continuous measurements for each individual animal, providing accurate reference methods used for research and inventory purposes. However, they require high labor input, animal training and are time consuming. In contrast, short-term measurement techniques (i.e., GreenFeed, sniffer method, facemask, laser CH4 detector and portable accumulation chamber) contain additional variations in timing and frequency of measurements obtained relative to the 24 h feeding cycle. However, they are suitable for large-scale measurements under commercial conditions due to their simplicity and high throughput. Successful use of these techniques relies on optimal matching between the objectives of the studies and the mechanism of each method with consideration of animal behavior and welfare. This review can provide useful information in selecting suitable techniques for CH4 emission measurement in ruminants.